Smoking Cessation Knowledge among Community Pharmacists in Saudi Arabia - Waleed M. Altowayan; Abdulmajeed A. Alqasoumi; Muhammad K. Rasheed; Abdulrhman I. Mohana; Amal S. Alharbi; Mohammad S. Alshammari (The Open Public Health Journal, 2026)
Introduction Tobacco use remains one of the most pressing global public health challenges, contributing substantially to the incidence of preventable diseases and premature mortality. In Saudi Arabia, tobacco consumption continues to rise, with an estimated 21.4% of adults identified as smokers and approximately 70,000 tobacco-related deaths reported annually. Methods This cross-sectional quantitative study was conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines developed by the National Institute for Health. A structured questionnaire comprising 26 items was administered and divided into two main sections: Section A focused on participants’ demographic characteristics, while Section B assessed the knowledge and attitudes of community pharmacists regarding the provision of smoking cessation services. A total of 206 community pharmacists participated in this study. Results The findings revealed that 89.8% (n = 185) of the respondents felt confident in advising customers who smoke to quit, indicating a high level of professional self-assurance in delivering smoking cessation counseling. Moreover, approximately 80% (n = 166) of the pharmacists reported awareness of the availability of smoking cessation clinics in Saudi Arabia and acknowledged the possibility of referring smokers to these specialized facilities for further treatment. Discussion Most pharmacists (89.8%) felt confident in advising smokers to quit, and about 80% were aware of smoking cessation clinics in Saudi Arabia and could refer smokers for further treatment. Conclusion Overall, the study demonstrated that community pharmacists in Saudi Arabia possess considerable knowledge and confidence in promoting smoking cessation initiatives. Nonetheless, the results also suggest that further evaluation and enhancement of pharmacists’ understanding of smoking cessation therapies are necessary to optimize their role in tobacco control and patient support.